2017
DOI: 10.3389/fpsyg.2017.01105
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Working Memory Capacity on Attentional Control under Pressure

Abstract: The present study aimed to examine the effects of working memory capacity (WMC) and state anxiety (SA) on attentional control. WMC was manipulated by (a) dividing participants into low- and high-WMC groups (Experiment 1), and (b) using working memory training to improve WMC (Experiment 2). SA was manipulated by creating low- and high-SA conditions. Attentional control was evaluated by using antisaccade task. Results demonstrated that (a) higher WMC indicated better attentional control (Experiments 1 and 2); (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Our EEG results in the low-WMC and anxiety group were consistent with previous findings, which suggest that attention control ability declines under anxiety in low-WMC individuals. For instance, a previous study found that state anxiety impaired attention control and that low-WMC individuals were worse at attention control in an anti-saccade task (Luo et al., 2017). An ERP study using the same experimental task provided further evidence that high-anxiety individuals exhibited lower ERP activity at the frontocentral and central recording sites compared with low-anxiety individuals (Ansari & Derakshan, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our EEG results in the low-WMC and anxiety group were consistent with previous findings, which suggest that attention control ability declines under anxiety in low-WMC individuals. For instance, a previous study found that state anxiety impaired attention control and that low-WMC individuals were worse at attention control in an anti-saccade task (Luo et al., 2017). An ERP study using the same experimental task provided further evidence that high-anxiety individuals exhibited lower ERP activity at the frontocentral and central recording sites compared with low-anxiety individuals (Ansari & Derakshan, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This result is in line with the comprehensive effects of WM-related attention guides; that is, both attention capture and attention suppression could occur. A previous study has shown that attention can be actively terminated after attention capture by the task-relevant features, accompanied by the neural index of active suppression (Pd) after attention capture (N2pc) (Sawaki et al., 2012); another study also suggested that moderate anxiety had little negative effect but could benefit attention control in the anti-saccade task (Luo et al., 2017). In the current study, the Pd component was induced in the low-WMC and anxiety group but not in the low-WMC and control group despite the absence of interaction between WMC and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility that can explain why healthy individuals reacted similarly to OCD subjects under high cognitive load may be related to working memory capacity. Working memory capacity is about the ability to control attention and inhibit interference from distractors and it has been proposed that high working memory capacity increases top-down attentional control (Luo et al, 2017). Redick and Engle (2006) used the ANT to examine the three attention networks (alerting, orienting, executive control of attention) in healthy individuals with high compared to low working memory span and found that group differences were only found in the executive control network, revealing increased attentional control in the high working memory capacity group.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been recently described that attentional control can either improve or deteriorate under pressure in an experimental setting. [ 24 ]…”
Section: Discussionmentioning
confidence: 99%